2008
DOI: 10.1016/j.ccr.2008.04.018
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic and Epigenetic Silencing of MicroRNA-203 Enhances ABL1 and BCR-ABL1 Oncogene Expression

Abstract: The mammalian genome contains several hundred microRNAs that regulate gene expression through modulation of target mRNAs. Here, we report a fragile chromosomal region lost in specific hematopoietic malignancies. This 7 Mb region encodes about 12% of all genomic microRNAs, including miR-203. This microRNA is additionally hypermethylated in several hematopoietic tumors, including chronic myelogenous leukemias and some acute lymphoblastic leukemias. A putative miR-203 target, ABL1, is specifically activated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
221
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 424 publications
(233 citation statements)
references
References 53 publications
8
221
0
4
Order By: Relevance
“…Recently, hypermethylation of miR-203 promoter has been found in HCC, cervical cancer and CML [12,13,17,32]. In this study, we confirmed that the mechanism of miR-203 downregulation was closely associated with the hypermethylation in its promoter region.…”
Section: Discussionsupporting
confidence: 85%
“…Recently, hypermethylation of miR-203 promoter has been found in HCC, cervical cancer and CML [12,13,17,32]. In this study, we confirmed that the mechanism of miR-203 downregulation was closely associated with the hypermethylation in its promoter region.…”
Section: Discussionsupporting
confidence: 85%
“…MIR127, MIR9, MIR148, MIR203, MIR340, MIR18, and MIR34b/c are several examples of DNA methylation regulated miRNAs. 14,23,[31][32][33] In the case of MIR34b/c, this locus has been reported to be epigenetically regulated in several cancers 31,34 Recently, MIR34b/c was shown to be a tumor suppressor mediating p53 activation in both colon and gastric cancers. 23,33,35 In addition, methylation of MIR124 families was initially described in colorectal cancer and was subsequently reported in tumors or other origins.…”
Section: Discussionmentioning
confidence: 99%
“…Следо-вательно, разработка метода «блокады» этого взаимо-действия является перспективной стратегией таргетной терапии опухолей данной локализации. miR-203 регулирует стабильность РНК, транскри-бируемой с гена ABL1 и его онкогенного варианта BCR-ABL1, образующегося в результате филадельфийской транслокации [76]. Эпигенетическое «выключение» miR-203 активирует синтез гибридного патологическо-го белка BCR-ABL1, что приводит к ускорению роста опухолевых клеток.…”
Section: Introductionunclassified